TO THE ISSUE OF IMPROVING QUALITY OF PERFORMANCE THE EVALUATION OF RAILWAY TRACK - Bondarenko, I. O. (Science and Transport Progress, 2007)
For consideration of questions on providing of terms of smoothness of motion and optimization of work of railway way it is suggested to enter the concepts of the systems of high-quality estimation of capacity and unfolded diagnostics